Maternal cardiovascular and endothelial function from first trimester to postpartum - Kolovetsiou-Kreiner, Vassiliki; Moertl, Manfred Georg; Papousek, Ilona; Schmid-Zalaudek, Karin; Lang, Uwe; Schlembach, Dietmar; Cervar-Zivkovic, Mila; Lackner, Helmut Karl (PloS one, 2018)
To explore noninvasively the complex interactions of the maternal hemodynamic system throughout pregnancy and the resulting after-effect six weeks postpartum. Eighteen women were tested beginning at the 12th week of gestation at six time-points throughout pregnancy and six weeks postpartum. Heart rate, heart rate variability, blood pressure, pulse transit time (PTT), respiration, and baroreceptor sensitivity were analyzed in resting conditions. Additionally, hemoglobin, asymmetric and symmetric dimethylarginine and Endothelin (ET-1) were obtained. Heart rate and sympathovagal balance favoring sympathetic drive increased, the vagal tone and the baroreflex sensitivity decreased during pregnancy. Relative sympathetic drive (sympathovagal balance) reached a maximum at 6 weeks postpartum whereas the other variables did not differ compared to first trimester levels. Postpartum diastolic blood pressure was higher compared to first and second trimester. Pulse transit time and endothelial markers showed no difference throughout gestation. However, opposing variables PTT and asymmetric dimethylarginine (ADMA) were both higher six weeks postpartum. The sympathetic up regulation throughout pregnancy goes hand in hand with a decreased baroreflex sensitivity. In the postpartum period, the autonomic nervous system, biochemical endothelial reactions and PTT show significant and opposing changes compared to pregnancy findings, indicating the complex aftermath of the increase of blood volume, the changes in perfusion strategies and blood pressure regulation that occur in pregnancy.